Can organic agriculture cope without copper for disease control? - Andrivon, Didier (éditions Quae, 2019)
Copper is used to control various fungal and bacterial diseases, especially in organic farming where synthetic fungicides are prohibited. The use of copper is subject to increasing regulatory restrictions in Europe due to its adverse effects on the environment. This book synthesizes the results of INRA scientific expertise on 'alternatives' to copper.